Indirect veneer treatment of anterior maxillary teeth with enamel hypoplasia - Devi Eka Juniarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Nowadays, aesthetic rehabilitation becomes a necessity. It is affected by patient’s background, especially career, social and economic status. The aesthetic abnormality of anterior teeth i.e discoloration, malposition and malformation can affect patient’s appearance, especially during smile. These dental abnormalities, as a result, can decrease patient’s performance. Dental malformation, for instance, can be caused by developmental tooth defect, such as enamel hypoplasia. Enamel hypoplasia is a developmental defect caused by the lack of matrix amount which leads to thin and porous enamel. Enamel hypoplasia can also be caused by matrix calcification disturbance starting from the formation and development of enamel matrix causing defect and permanent changes which can occur on one or more tooth. Purpose: The aim of the study is to improve dental discoloration and tooth surface texture on anterior maxillary teeth with enamel hypoplasia by using indirect veneer with porcelain material. Case: A 20 years-old woman with enamel hypoplasia came to the Dental Hospital, Faculty of Dentistry Airlangga University. The patient wanted to improve her anterior maxillary teeth. It is clinically known that there were some opaque white spots (chalky spotted) and porous on anterior teeth’s surface. Case management: Indirect veneer with porcelain material had been chosen as a restoration treatment which has excellent aesthetics and strength, and did not cause gingival irritation. As a result, the treatment could improve the confidence of the patient, and could also make their function normal. Conclusion: Indirect veneer is an effective treatment, which can improve patient’s appearance and self confidence.Latar belakang: Saat ini perbaikan estetik menjadi suatu kebutuhan. Kebutuhan akan estetik dipengaruhi latar belakang penderita, terutama karir, status sosial dan ekonomi. Hal ini disebabkan, kelainan estetik seperti diskolorasi, malposisi, malformasi, dapat mempengaruhi penampilan penderita terutama saat tersenyum. Kelainan gigi tersebut pada akhirnya dapat memperburuk penampilan penderita. Malformasi gigi dapat disebabkan oleh kelainan pada masa perkembangan gigi, misalnya hipoplasia enamel. Hipoplasia enamel adalah kelainan perkembangan yang disebabkan sedikitnya matriks enamel sehingga terjadi ketipisan dan porusnya enamel. Hipoplasia enamel dapat disebabkan gangguan kalsifikasi matriks saat pembentukan dan perkembangan matriks enamel, kerusakan dan perubahan permanen ini dapat melibatkan satu atau beberapa gigi. Tujuan: Tujuan perawatan ini memperbaiki diskolorasi dan tekstur permukaan gigi depan rahang atas akibat hipoplasia enamel menggunakan veneer indirek berbahan porselen. Kasus: Seorang penderita wanita 20 tahun dengan hipoplasia enamel datang ke Rumah Sakit Gigi dan Mulut Pendidikan Fakultas Kedokteran Gigi Universitas Airlangga. Penderita ingin memperbaiki gigi depan rahang atas yang secara klinis tampak bercak putih opak seperti kapur dan porus pada permukan labial gigi. Tatalaksana kasus: Veneer indirek dengan bahan porselen dipilih sebagai restorasi oleh karena segi estetik, kekuatan dan tidak mengiritasi ginggiva. Restorasi ini dapat meningkatkan kepercayaan diri penderita dan memperbaiki fungsi gigi. Kesimpulan: Veneer indirek merupakan perawatan yang efektif, dapat meningkatkan penampilan dan kepercayan diri penderita.